Denitrifiers, nitrogen-fixing bacteria and N2O soil gas flux in high Arctic ice-wedge polygon cryosols. Issue 5 (29th April 2019) - Altshuler, Ianina; Ronholm, Jennifer; Layton, Alice; Onstott, Tullis C; W. Greer, Charles; Whyte, Lyle G
ABSTRACT: Climate warming and subsequent permafrost thaw may result in organic carbon and nutrient stores being metabolized by microbial communities, resulting in a positive feedback loop of greenhouse gas (GHG) soil emissions. As the third most important GHG, understanding nitrous oxide (N2 O) flux in Arctic mineral ice-wedge polygon cryosols and its relationship to the active microbial community is potentially a key parameter for understanding future GHG emissions and climatic warming potential. In the present study, metatranscriptomic analyses of active layer Arctic cryosols, at a representative ice-wedge polygon site, identified active nitrogen-fixing and denitrifying bacteria that included members of Rhizobiaceae, Nostocaceae, Cyanothecaceae, Rhodobacteraceae, Burkholderiaceae, Chloroflexaceae, Azotobacteraceae and Ectothiorhodospiraceae. Unique microbial assemblages with higher proportion of Rhodobacteriales and Rhocyclales were identified by targeted functional gene sequencing at locations with higher ( P = 0.053) N2 O emissions in the wetter trough soils compared with the dryer polygon interior soils. This coincided with a higher relative abundance of the denitrification nirS gene and higher nitrate/nitrite concentrations in trough soils. The elevated N2 O flux observed from wetter trough soils compared with drier polygon interior soils is concerning from a climate warming perspective, since the Arctic is predicted to become warmer and wetter. Abstract : An active community of denitrifying and nitrogen-fixing bacteria is associated with differential N2 O soil gas fluxes in high Arctic ice-wedge polygon cryosols.